Improving cycling culture in cities. Training Reader: 3rd PRESTO on-site training session. [Transnational Training in Zagreb, 8.-9-12.2010]. - (:unkn) unknown (My University, 2010)
The reader constitutes a post-meeting compilation of the sessions' contents, discussions and main results and provides a brief but comprehensive summary of this third transnational PRESTO on-site training session in Zagreb. Participants of this training session in Zagreb had the opportunity to find out best practices and exchange ideas with European specialists on the following topics: Integration of cycling with public transport; Safe cycling campaigns and promotion campaigns; Cycling in pedestrian areas and shared spaces; Pedelecs promotion.
Keywords: Individualverkehr; Fahrradverkehr; Öffentlichkeitsarbeit; Verkehrssicherheit; Fahrradförderung; Projekt; Fahrradinfrastruktur; Fahrradfreundliche Stadt; Shared Space; Pedelec; Fahrradmitnahme; Fahrradstation; Bike and Ride; Elektrofahrrad